Functional aplasia of the contralateral A1 segment influences clinical outcome in patients with occlusion of the distal internal carotid artery - Fischer, Sebastian; Goertz, Lukas; Weyland, Charlotte S.; Khanafer, Ali; Maurer, Christoph J.; Zimmermann, Hanna; Fischer, Thomas David; Styczen, Hanna; Tan, Benjamin; Alexandrou, Maria; Lobsien, Donald; Lobsien, Elmar; et al. (Journal of Clinical Medicine, 2022)
Background: The importance of an A1 aplasia remains unclear in stroke patients. In this work, we analyze the impact of an A1 aplasia contralateral to an acute occlusion of the distal internal carotid artery (ICA) on clinical outcomes. Methods: We conducted a retrospective study of consecutive stroke patients treated with mechanical thrombectomy at 12 tertiary care centers between January 2015 and February 2021 due to an occlusion of the distal ICA. Functional A1 aplasia was defined as the absence of A1 or hypoplastic A1 (>50% reduction to the contralateral site). Functional independence was measured by the modified Rankin Scale (mRS ≤ 2). Results: In total, 81 out of 1068 (8%) patients had functional A1 aplasia contralateral to distal ICA occlusion. Patients with functional contralateral A1 aplasia were more severely affected on admission (median NIHSS 18, IQR 15-23 vs. 17, IQR 13-21; aOR: 0.672, 95% CI: 0.448-1.007, p = 0.054) and post-interventional ischemic damage was larger (median ASPECTS 5, IQR 1-7, vs. 6, IQR 3-8; aOR: 1.817, 95% CI: 1.184-2.789, p = 0.006). Infarction occurred more often within the ipsilateral ACA territory (20/76, 26% vs. 110/961, 11%; aOR: 2.482, 95% CI: 1.389-4.437, p = 0.002) and both ACA territories (8/76, 11% vs. 5/961, 1%; aOR: 17.968, 95% CI: 4.979-64.847, p ≤ 0.001). Functional contralateral A1 aplasia was associated with a lower rate of functional independence at discharge (6/81, 8% vs. 194/965, 20%; aOR: 2.579, 95% CI: 1.086-6.122, p = 0.032) and after 90 days (5/55, 9% vs. 170/723, 24%; aOR: 2.664, 95% CI: 1.031-6.883, p = 0.043). Conclusions: A functional A1 aplasia contralateral to a distal ICA occlusion is associated with a poorer clinical outcome.